The Role of Entreprenurial Education on Enhancing Entrepeneurial Intentions on Indonesian Students - Aquinaldo Sistanto Putra; Edy Suroso; Dian Kurniawan; Alfin Nurfahmi Mufreni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study investigated the role of entrepreneurial education on entrepreneurial intention by applying the modified TPB model with opportunity recognition. Our research involved 395 Indonesian high school and undergraduate students aged 15–25 years with structural equation modeling partial least squares (SEM-PLS) for data analysis. The results showed the crucial role of entrepreneurial education on antecedents of entreprenurial intention, but no direct effect on entrepreneurial intention. Entrepreneurial education also indirectly foster entrepreneurial intention by strengthening positive attitudes, self-efficacy, and opportunity recognition skills. The study provides insight about the interaction between entrepreneurial education with individual traits and social norms in developing entrepreneurial intention, particulary with the ability to seize the entrepreneurial opportunity.